Cardiovascular events follow-up analysis in patients with sinus node dysfunction and implanted pacemaker - E. A. Badykova; M. R. Badykov; V. V. Plechev; I. Sh. Sagitov; I. A. Lakman; N. Sh. Zagidullin (Российский кардиологический журнал)
Dysfunction of sinus node (DSN) is the syndrome, characterized by symptoms of tissue hypoperfusion and manifestations on the electrocardiogram and could potentially lead to sudden death. The various impact of different types of pacemakers on life quality and cardiovascular endpoints was shown.Aim. To analyze follow-up cardiovascular endpoints in patients with DSN and installed pacemakers.Material and methods. Six hundred and ten patients with DSN were analyzed in follow-up period (39,7±0,8 months) for unfavorable cardiovascular events (myocardial infarction, strokes, cardiovascular and non-cardiovascular hospitalizations).Results. Mortality rate differed depending on DSN variant (p=0,041), and most unfavorable was “tachy-brady” and sinoatrial node arrest + sinus node block III types. Also, the difference in mortality rate was shown for pacing variants (p=0,049) with maximal rate number of deaths was in ventricular pacemakers (24,6%) less — in dual-chamber pacemakers (11,7%) and minimal — in atrial (5,5%). No changes in cardiovascular endpoints was found between groups with sinus and pacemaker’s rhythm (p>0,5).Conclusion. In the follow-up analyze the difference between cardiovascular endpoints in patients in various types of pacemakers and regimen of stimulation was shown.